2019
DOI: 10.1080/02713683.2019.1663385
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in Glaucoma: Towards Clinical Trials and Precision Medicine

Abstract: Purpose: The eye is currently at the forefront of translational medicine and therapeutics. However, despite advances in technology, primary open-angle glaucoma remains the leading cause of irreversible blindness worldwide. Traditional intraocular pressure (IOP)-lowering therapies are often not sufficient to prevent progression to blindness, even in patients with access to high-quality healthcare. Neuroprotection strategies, which aim to boost the ability of target cells to withstand a pathological insult, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 106 publications
(101 reference statements)
0
32
0
4
Order By: Relevance
“…In addition, regeneration of nonviable RGCs and their axons would be highly desirable to restore and maintain functional vision. However, randomized clinical trials investigating oral memantine and topical brimonidine have not demonstrated a clear neuroprotection benefit in patients with glaucoma [11,15]. For the latter pharmacologic agent, patients with low-pressure glaucoma had slightly less visual field progression with topical administration of the alpha2-adrenergic agonist brimonidine tartrate 0.2% compared to the beta-adrenergic antagonist timolol maleate 0.5% [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, regeneration of nonviable RGCs and their axons would be highly desirable to restore and maintain functional vision. However, randomized clinical trials investigating oral memantine and topical brimonidine have not demonstrated a clear neuroprotection benefit in patients with glaucoma [11,15]. For the latter pharmacologic agent, patients with low-pressure glaucoma had slightly less visual field progression with topical administration of the alpha2-adrenergic agonist brimonidine tartrate 0.2% compared to the beta-adrenergic antagonist timolol maleate 0.5% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently accepted strategies for treatment of POAG, whether medical, laser, or incisional surgical modalities, aim to lower IOP below a presumed threshold level [ 4 , 8 , 9 ]. Though these IOP-lowering therapies have been proven to slow and/or halt progression of the glaucomatous damage and therefore are neuroprotective in nature, slow progress has been made in developing IOP-independent neuroprotection and/or neuroregeneration strategies [ 10 , 11 ]. While neuroprotection strategies to enhance the ability of target cells in the central nervous system (CNS) to withstand pathological insults have shown substantive promise in animal models, none have been reported to be clinically effective in human clinical trials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Hence, innovative approaches of neuroprotection are necessary to develop more potential options for glaucoma treatment. 4 Oxidative stress is presumed to play a crucial role in the neurodegenerative process of glaucoma. 5 Apart from its neurodegenerative effect on the optic nerve, oxidative stress has also been shown to damage another major target tissue of glaucoma: trabecular meshwork (TM).…”
mentioning
confidence: 99%
“… 3 Hence, innovative approaches of neuroprotection are necessary to develop more potential options for glaucoma treatment. 4 …”
mentioning
confidence: 99%